Photocatalytic oxidation of dinitronaphthalenes: Theory and experiment - Bekbolet, Miray; Cinar, Zekiye; Kilic, Murat; Uyguner, Ceyda Senem; Minero, Claudio; Pelizzetti, Ezio (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
A combination of photocatalytic oxidation experiments and quantum mechanical calculations was used in order to describe the mechanism and the nature of the photocatalytic oxidation reactions of dinitronaphthalane isomers and interprete their reactivities within the framework of the Density Functional Theory (DFT). The photocatalytic oxidation reactions of three dinitronaphthalene isomers, 1,3-dinitronaphthalene, 1,5-dinitronaphthalene and 1,8-dinitronaphthalene in the presence of TiO2 Degussa P-25 grade were investigated experimentally. The reactions were carried out in a Solarbox photoreactor equipped with a Xenon lamp. The removal of the individual substrates was followed by means of a gas chromatographic method. Nonpurgable organic carbon contents of the samples were determined by means of the catalytic oxidation method using Total Organic Carbon analyzer. With the intention of determining the best reactivity descriptors to explain the differences in the photocatalytic oxidation rates in terms of the molecular properties, geometry optimizations of the compounds were performed with the Density Functional Theory DFT at B3LYP/6-31G* level. In order to take the effect of adsorption on the oxidation rate, a cluster Ti9O18 cut from the anatase bulk structure was modeled. The binding energies for the compounds were calculated by using the double-zeta basis set. Global hardness, softness, Fukui functions, local hardness-softness and local softness differences were calculated. The results show that the reactions investigated are orbital-controlled and electrophilic in nature. Local DFT descriptors reflect the reactivities of the dinitronaphthalene isomers better than the global ones, due to the differences in their adsorptive capacities. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Dinitronaphthalenes; Photocatalytic oxidation; DFT descriptors; Reactivity indices; Adsorption model; POLYCYCLIC AROMATIC-HYDROCARBONS; CONTAINING BENZENE-DERIVATIVES; DENSITY-FUNCTIONAL THEORY; REACTIVITY INDEXES; DEGRADATION; NITROGEN; SUBSTITUTION; TOXICITY; TOLUENE; TIO2; Environmental Sciences & Ecology